2015
DOI: 10.1016/j.ceramint.2015.04.132
|View full text |Cite
|
Sign up to set email alerts
|

Effect of titania addition on the properties of freeze-cast alumina samples

Abstract: This work investigated the behavior of TiO 2 -containing α-Al 2 O 3 samples prepared by the freeze-casting technique. Camphene and liquid nitrogen were used as the solvent and cooling fluid, respectively. Camphene resulted in the formation of dendritic pores, in the direction of the freeze-casting cold front during sample preparation. The formation of β-Al 2 TiO 5 phase occurred at 1300 °C, and became more evident as the sintering temperatures reached 1500 °C. The TiO 2 loading did not affect the sample porosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 58 publications
1
13
0
1
Order By: Relevance
“…These slurries were sealed in a 40 mL plastic bag and mixed by sonicating at 42 kHz for 12 min. Using sonication to mix the slurries is similar to methods that have proven effective in the past reports on freeze‐cast slurries . Immediately following mixing, the individual slurries were poured into a PVC freeze‐cast mold of diameter 20 mm and then directionally frozen from room temperature at a rate of 10°C min −1 within a custom Helmholtz‐coil‐based magnetic freeze‐caster, as illustrated in Figure .…”
Section: Methodsmentioning
confidence: 99%
“…These slurries were sealed in a 40 mL plastic bag and mixed by sonicating at 42 kHz for 12 min. Using sonication to mix the slurries is similar to methods that have proven effective in the past reports on freeze‐cast slurries . Immediately following mixing, the individual slurries were poured into a PVC freeze‐cast mold of diameter 20 mm and then directionally frozen from room temperature at a rate of 10°C min −1 within a custom Helmholtz‐coil‐based magnetic freeze‐caster, as illustrated in Figure .…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that TiO 2 is a good mineralizer for promoting the crystallization of the MA and A 3 S 2 . In addition, TiO 2 was frequently employed to enhance the sintering of Al 2 O 3 ceramics through the formation of Al 2 O 3 ‐TiO 2 solid solution . Therefore, TiO 2 was added in this work to guarantee the formation of MA and A 3 S 2 in Al 2 O 3 ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] In addition, TiO 2 was frequently employed to enhance the sintering of Al 2 O 3 ceramics through the formation of Al 2 O 3 -TiO 2 solid solution. [21][22][23][24] Therefore, TiO 2 was added in this work to guarantee the formation of MA and A 3 S 2 in Al 2 O 3 ceramics. However, the simultaneous addition of TiO 2 and talc for sintering Al 2 O 3 ceramics has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…The freeze-cast samples were obtained following a method as published elsewhere [32]. Subsequently, the slurries were poured into a freeze casting rig containing a high thermal conductivity copper plate and a polytetrafluoroethylene (PTFE) mold.…”
Section: Synthesismentioning
confidence: 99%
“…For instance, it is well known that doping titania into alumina tends to form an aluminum titanate (Al 2 TiO 5 ) phase with superior mechanical strength than alumina [31]. Recently, it was reported that TiO 2 doping with loadings above 4 wt% reduced the mechanical strength in freezecast alumina which was associated with the formation of microcracks [32]. Hence, metal oxide doping must be controlled to a point where it is no longer beneficial.…”
Section: Introductionmentioning
confidence: 99%